Mathematics Problem-Solving Skill Reviewed from Self-Regulated Learning of the Eleventh Graders - Istiqomah, Novita Ayu; Waluya, St. Budi; Isnarto, Isnarto (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe the learners’ problem-solving skills reviewed from the self-regulated learning of the eleventh graders. Self-regulated learning in this research did not function as a learning method. It was instead a self-planning and monitoring process toward the affective process to solve the academic tasks. The applied method in this research was descriptive qualitative. The data collection techniques in this research were observation, test, questionnaire, and interview. The subjects were determined by the purposive sampling technique. The subject selection resulted in six subjects. Every two subjects were categorized into high, moderate, and low self-regulated learning. The findings showed that (1) the eleventh graders with high self-regulated learning autonomously joined the online learning and had self-confidence in their skills; (2) the moderate-self regulated learners committed a few mistakes while calculating, writing the units, and reflecting their mathematics problem-solving process; (3) the low-self regulated learners had low-mathematics problem-solving skill since they could only apply and adjust the strategy to solve the problems.